Comparison of the Efficiency of Some Non-Thermal Techniques in Detoxifying Aflatoxin B1, Ochratoxin A, and Fumonisin B1 from Feeds of Poultry - Alnaemi, Hiba; Dawood, Tamara; Algwari, Qais (The Iraqi Journal of Veterinary Medicine, 2025)
Atmospheric pressure corona discharge (APCD), ultraviolet C with ozone (UVC w/ O3), and plasma treated water (PTW) have lately been spotlighted in the food industry as non-thermal techniques (NTTs) for detoxifying mycotoxins, due to their unique features. The efficiency of these techniques in detoxifying aflatoxin B1 (Afla B1), ochratoxin A (Ochra A), and fumonisin B1 (Fum B1) in feeds of poultry and their effects on quality of feed were inspected. Samples of feed were subjected to APCD, UVC w/ O3, and PTW for 10, 20, and 60 min. Mycotoxin concentrations were determined by competitive enzyme-linked immunosorbent assay (ELISA), and outcomes were verified by high-performance liquid chromatography (HPLC). Standard analytical methods were adopted for analyzing feed components and determining peroxide values (PVs). Subjecting samples to APCD, UVC w/ O3, and PTW for 10 min resulted in degradation of Afla B1 to levels of 46.6, 38.9, and 28.9%, Ochra A to 49.8, 35.9, and 29.9%, and Fum B1 to 58.6, 42.6, and 35.9%, respectively, for 20 min to Afla B1 levels of 57.7, 46.6, and 32.9%, Ochra A 68.9, 45.3, and 38.5%, and Fum B1 75.7, 49.9, and 41.6%, respectively, for 60 min to Afla B1 levels of 83.2, 65.7, and 33.8%, Ochra A 84.2, 73.6, and 40.7%, and Fum B1 84.8, 71.2, and 43.4%, respectively. The main conclusion of the study is that APCD and UVC w/ O3 can be adopted to efficiently degrade Afla B1, Ochra A, and Fum B1 in feed while maintaining its quality. According to their impact on feed quality, techniques can be ranked as follows: APCD > UVC w/ O3 > PTW‎‎‎.